Development of Healthy Products Using Spider Conch (Gastropoda stromboidea) - Garces, Jr., Sulpicio D.; Pepito, Mario Ramil; Minoza, Kevin L.; Diaz, Welou Dil B.; Tejas, Edison C. (JPAIR Multidisciplinary Research, 2016)
For years now, most doctors have insisted that an average diet that consists of healthy seafood at least twice a week can improve the quality of life (No, Meyers, Prinyawiwatkul, & Xu, 2007). The study utilized an experimental method in developing healthy products out of spider conch (Gastropoda stromboidea) shellfish. Spider conch extract was used in the formulation of sauce as an alternative product while the spider conch meat after the extraction was used for the development of the spread and patty. Panel responses were analyzed using 7 and 9-point hedonic scales. One Way Analysis of Variance was also used to determine whether a significant difference existed between and among the experimental lots. Findings showed that spider conch extract is good for sauce formulation, and the spider conch meat are good in preparing spread. Also, the study reveals that there is no significant difference between the variants of spider conch sauce and spread for taste; patty for aroma attributes, therefore, the null hypothesis was accepted. It was concluded that the developed spider conch sauce is a better alternative product that the commercial sauces available in the market regarding vitamins, protein, and iodine content.Â The researchers recommend the use of Cooking Manual and Procedures for HRM students.